2018
DOI: 10.1016/s1348-8643(18)30008-9
|View full text |Cite
|
Sign up to set email alerts
|

Trismus‐pseudocamptodactyly syndrome with bilateral hypoplastic mandibular condyles and shallow mandibular fossa: A case report

Abstract: Trismus‐pseudocamptodactyly syndrome (TPS) (OMIM#158300), also known as Hecht syndrome, is a rare autosomal dominant distal arthrogryposis. Bilateral hyperplasia of the coronoid processes has been reported to cause trismus. In this study, we report a case of TPS definitively diagnosed on the basis of clinical signs in a patient who had bilateral hypoplastic mandibular condyles and shallow mandibular fossa; TPS in such patients have never been reported in the literature. On the basis of the present case, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Furthermore, our patient denied any known family history of similar manifestations. A review of related literature on patients presenting with both camptodactyly and TMD over the past four decades revealed that these manifestations occurred in the context of the auriculo-condylar syndrome (ACS) and trismuspseudocamptodactyly syndrome (TPS) [5][6][7][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our patient denied any known family history of similar manifestations. A review of related literature on patients presenting with both camptodactyly and TMD over the past four decades revealed that these manifestations occurred in the context of the auriculo-condylar syndrome (ACS) and trismuspseudocamptodactyly syndrome (TPS) [5][6][7][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…TPS (Hecht-Beals syndrome or Dutch-Kentucky syndrome) is caused by a mutation in the myosin heavy chain 8 (MYH8) gene affecting early skeletal development. All reviewed cases documented camptodactyly and trismus with or without coronoid hyperplasia [ 5 , 14 ]. In contrast, we identified only one report of a patient (with significant family history) affected with ACS who had concurrent camptodactyly and TMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation